A high throughput screen for 17 Dermorphin peptides in equine and human urine and equine plasma. Issue 9 (20th November 2013) - Steel, Rohan; Timms, Mark; Levina, Vita; Vine, John
<x xml:space="preserve">Abstract</x> The Dermorphins are a family of peptides that act as potent agonists of the opioid μ receptor. Originally identified as a seven amino acid peptide on the skin of the South American Phyllomedusa frog, peptide chemists have since developed a large number of Dermorphin variants, many with superior opioid activity to the original peptide. Dermorphins are unique among the peptide opioid agonists as they appear to have a limited ability to cross the blood brain barrier, producing effects on both the central and peripheral nervous systems. It is this ability of Dermorphins to provide central anaesthesia after intravenous or subcutaneous administration that allows their use as analogues of the opioid class of drugs. Recently, illicit use of the Dermorphin peptide in the racing industry has shown the need for an analytical method to control the use of these peptides. We present a high‐throughput liquid chromatography‐tandem mass spectrometry screen for 17 Dermorphin peptides in equine urine and plasma with limits of detection down to 5 pg/mL. The peptide extraction technique is also suitable for use in human urine. Copyright © 2013 John Wiley & Sons, Ltd.